The introduction of a paediatric nutrition support program led by a clinical dietitian at a low-resource hospital setting in Malawi - Allison I. Daniel; Humphrey Chatenga; Bernadette Chimera; Emmie Mbale; Mphatso Chisala; Eric Borgstein; Josephine Langton; Carmen Gonzalez; Robert H. J. Bandsma; Laura Vresk (Taylor & Francis Group, 2019)
In low- and middle-income countries, nutrition support strategies are often suboptimal or non-existent in hospital settings. This is further compounded by high rates of malnutrition in these countries. The first four dietitians graduated in Malawi in 2017 providing a new opportunity to build capacity to introduce nutrition support in an acute care setting. A paediatric nutrition support program was implemented at Queen Elizabeth Central Hospital (QECH) in Blantyre, Malawi including the hiring of a local dietitian. This capacity building paper explains the development and introduction of the nutrition support program including a description of perceptions of health professionals at QECH working alongside the dietitian. In the first four months of the program at QECH, the dietitian provided nutrition support to 183 different patients across paediatric wards. Nutritional interventions predominantly included infant formula and breastmilk fortification, provision of therapeutic feeds orally or via nasogastric tubes, increased dietary protein intake for children identified to be at high risk, and nutritional counselling to caregivers. More complex nutritional interventions were also given such as the insertion of gastrostomy tubes to deliver nutrition directly to the stomach. Following the introduction of the program, qualitative interviews were done with health professionals at QECH including nurses (n = 5) and physicians (n = 11). All participants emphasized the importance and impact of the nutrition support program in enhancing the care of hospitalized children, therefore improving outcomes such as tolerability of clinical interventions, decreased duration of stay, and reduced risk of hospital readmission. In conclusion, there is a need for nutrition support provided by a dietitian for different paediatric patients which was corroborated by positive feedback from health professionals at QECH. Integration of dietitians into the healthcare system by respective Ministries of Health will require advocacy around the potential for nutrition support to strengthen the quality of care of vulnerable children. A Chichewa abstract for this paper is available in a supplementary file.